(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The COVID-19 pandemic had a profound impact on the world in many ways, including on health spending and utilization. Expenditure on medicines and health care products plays an important role in the determination of its demand and thus production. This research article examines the changes in the consumer spending on medical and health care that have taken place as a result of the pandemic and concluded that the COVID-19 pandemic has brought to the forefront the importance of good health and the need for individuals to prioritize their health and wellness. The pandemic has also highlighted the necessity of having a robust healthcare system to tackle a pandemic of such magnitude. As a result, people have become more health conscious, and this has translated into increased spending on health. A careful planning and resource allocation will be needed to ensure that all individuals continue to receive the care they need. Primary data for the study is collected from 318 respondents, through a structured questionnaire and then analysed and presented using statistical tools.